Implementing Character Education Strengthening Through the Savings Movement: Building Intelligent and Integrity-Driven Generations - Zam, Zam; Nurdjan, Sukirman; Saleh, Mahadin (International Journal of Asian Education, 2024)
This study examines the implementation of the Savings Movement at SDN 268 Towuti as a strategic effort to strengthen character education, with a particular focus on fostering honesty among students. Employing a qualitative case study approach, the research investigates how systematic planning, structured implementation, and active collaboration among stakeholders have contributed to positive behavioral changes. Key strategies include organized program management, integration of honesty into school routines, and strong coordination between teachers and parents. The program introduced creative initiatives such as market simulations, student-led financial reports, and a reward system to instill financial responsibility and ethical values. Findings reveal that the program effectively nurtured core character traits such as honesty, discipline, responsibility, independence, and social awareness. Daily saving practices, routine monitoring, and consistent communication between home and school supported the internalization of these values. Market simulations provided practical experiences in accountability and entrepreneurship, while the documentation of financial transactions taught transparency and reinforced integrity. The reward system further motivated students to maintain honest behaviors and allowed for parental involvement in the learning process. The study concludes that the Savings Movement presents a practical, replicable model for integrating character education into school systems. It demonstrates how embedding moral values into daily school activities, supported by structured strategies and community involvement, can lead to sustainable character development. This model offers valuable insights for educators seeking innovative approaches to embed character education into formal learning environments.